Effect of Backward Summary Technique on Reading Comprehension Enhancement among Non-English Majors - Samaneh Bahrami; Ramin Rahimy (Asociación Colombiana de Profesores de Ingles, 2022)
This study aimed to probe whether using the backward summary technique led to reading comprehension enhancement among non-English major university students at the Islamic Azad University of Babol, located in Babol city, in the North of Iran. 120 B.S. level nursing and microbiology students were randomly selected from a population of non-English majors enrolled for the General English course, divided into four groups of 30, and were randomly assigned to two experimental and two control groups. A pre-test of reading comprehension was administered to all groups, and then, they were taught passages t read for eight sessions but with different methods. A one-way ANCOVA was run to investigate the impact of the intervention, while controlling for the pre-test. The results indicated statistically significant effects for the experimental groups on the post-test, regarding comprehension, retention, and organization of the key concepts.